Fluvial environment and existing stability condition of the Manahara River, central Nepal Himalaya - Tamrakar, Naresh Kazi; Bajracharya, Ramita (Journal of Nepal Geological Society, 2009)
The Manahara River that is one of the large tributaries of the Bagmati River has been exploited in recent decade. Lateral shifting of river, bank erosion and subsequent destruction of fertile lands and inundation of crop lands during high discharge are some of the problems. Five representative segments of the river were surveyed in detail for existing status of the river applying hydrologic, geomorphologic and sedimentologic analyses in order to recognize stability condition. The first to the fifth segments are classified as F4-, C4-, C4-, B4- and B4-streams characterised by matrix supported gravelly substrates. Streams F4 and B4 are potential to degradation and streams C4 are potential to aggradation. Dimensionless shear stress in all the segments exceed critical dimensionless shear stress even at much lower bankfull condition suggesting greater mobility of the riverbed materials. Schumm's F-factor versus M-factor plots revealed that the 3rd and 4th order streams (B4-streams) are potential to degradation, and 5th order (F4 and C4)) streams are potential to aggradation. The existing channel surveyed in 2006 was compared with the previous channel of 1995. The results indicate that the meander belt area has grown by 8% and average meander belt width has increased by 32%. The average lateral shift of meander belt axis has approached 156 m with maximum shift of 243 m in C4 stream. The average meander length and the meander belt ax is length have extended respectively by 25% and 2.5%. Meander geometry of the 5th ordered streams deviates from the stability. All these suggest that the planform geometry of the Manahara River has not been stable. Therefore, system wide instability exists in the river basin. In order to improve the existing river condition, anthropogenic disturbances should be minimised , and bank protection measures and restriction of riverbed mining should be implemented in C4- and F4-streams before deteriorating the river into severe condition.